Individual and Environmental Risk Factors of Tuberculosis: A New Evidence from Ponorogo, East Java - Diana Sayidah; Setyo Sri Rahardjo; Bhisma Murti (Journal of Epidemiology and Public Health, 2018)
Background: For centuries, TB has been linked anecdotally with environmental risk factors that go hand-in-hand with poverty: indoor air pollution, tobacco smoke, malnutrition, over